Rules of thumb for chemical engineers : a manual of quick, accurate solutions to everyday process engineering problems - Branan, Carl (Elsevier, 2005)
This new edition of the most complete handbook for chemical and process engineers incorporates the latest information for engineers and practitioners who depend on it as a working tool. New material explores the recent trends and updates of gas treating and fractionator computer solutions analysis. Substantial additions to this edition include a new section on gasification that reflects the many new trends and techniques in the field and a treatment on compressible fluid flow. This convenient volume provides engineers with hundreds of common sense techniques, shortcuts, and calculations to quickly and accurately solve day-to-day design, operations, and equipment problems. Here, in a compact, easy-to-use format, are practical tips, handy formulas, correlations, curves, charts, tables, and shortcut methods that will save engineers valuable time and effort. * The standard handbook for chemical and process engineers * All new material on pinch point analysis on networks of heat exchangers and updates on gas treating in process design and heat transfer * Hundreds of common sense techniques and calculations.